2013
DOI: 10.1111/j.1756-1051.2012.01700.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic position of Cyperus clandestinus (Cypereae, Cyperaceae) clarified by morphological and molecular evidence

Abstract: Extreme morphological reduction and convergent evolution can obscure taxonomic relationships. This phenomenon is frequently encountered in Cyperaceae, where characters traditionally used to diagnose genera have been shown to have evolved independently multiple times. The Ethiopian high‐altitude perennial first described as Cyperus clandestinus was subsequently moved to Ficinia because it has spiral glume arrangement, unlike typical Cyperus species, which have distichous glume arrangement. However, this positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The first subclade, also retrieved in previous studies (e.g. Muasya et al ., , in press; Larridon et al ., ), is represented by Cyperus cuspidatus Kunth (and its Malagasy relative C. waterlotii Cherm . ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The first subclade, also retrieved in previous studies (e.g. Muasya et al ., , in press; Larridon et al ., ), is represented by Cyperus cuspidatus Kunth (and its Malagasy relative C. waterlotii Cherm . ).…”
Section: Discussionmentioning
confidence: 99%
“…Brongn. (two species) appears to be at the base of the Cyperus clade (Muasya et al ., , in press), but this needs further confirmation. Although molecular phylogenetic studies have revealed that all of these genera are nested in Cyperus (e.g.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Using a silica gel dried sample of the new taxon, DNA was extracted using the CTAB method and the ITS marker amplified and sequenced using standard protocols and primers (Muasya et al 2014). Contigs of forward and reverse sequences were assembled using the STADEN package (Staden 1996).…”
Section: Methodsmentioning
confidence: 99%